A study of acute flaccid paralysis cases reported from a tertiary care hospital in Delhi - Kumar, Ajay (Indian Journal of Child Health, 2015)
Background: As many countries including India become polio-free, Guillain–Barre syndrome (GBS) becomes the most common cause of the acute flaccid paralysis (AFP). Objective: To describe the socio-epidemiology and causes of AFP cases reported from a tertiary care hospital in Delhi. Materials and Methods: This was a cross-sectional descriptive study based on record review of the case investigation forms of AFP cases reported from January 2011 to December 2013. Results: Total 187 cases of AFP were reported during the study period. Majority (54.01%) of the cases were male. The mean age was 5 years 3 months (range - 1 month to 13 years 8 months). The age group most commonly affected was 5-12 years (43.32%) followed by 2-5 years (32.62%). Most (88.24%) of the cases belonged to low socio-economic status, with 79.68% of the cases from an urban area. Investigations were done within 48 h of the date of notification by medical personnel in 94.65% of cases. Two stool specimens were collected within 7 days of onset of weakness in 94.12% of cases and stool condition was good in all collected specimens. None of the stool samples tested positive for wild polioviruses and vaccine derived poliovirus. Non-polio enterovirus was isolated in 15 cases (8.02%) while results were not mentioned in 12 cases (6.42%). In six cases, vaccine virus was isolated. The most common cause of AFP was GBS (32.08%) followed by isolated facial palsy (8.56%) and viral myalgia (6.95%). Conclusion: GBS was most common cause of AFP followed by isolated facial palsy. The slum area and migratory population need more attention as the majority of AFP cases were from low socio-economic status family.